2012
DOI: 10.1186/1471-244x-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of psychiatric inpatients in New Zealand’s Waikato region

Abstract: Background Vitamin D deficiency is widespread in New Zealand, confers multiple health risks, and may be particularly common among people with psychiatric illness. We studied vitamin D status in an unselected sample of adult psychiatric inpatients in Hamilton (latitude 37.5 S) during late winter. Methods We recruited 102 consenting subjects and measured 25-hydroxy vitamin D3 levels in venous blood using a competitive electrochemiluminescence immunoassay. In addition to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 25 publications
5
26
2
Order By: Relevance
“…Regarding medication, in our patient sample we found no relationship between exposure to antipsychotic medication and 25(OH)D insufficiency, which is consistent with reports of patents with schizophrenia (Itzhaky et al, 2012), and of first-episode psychosis patients (Crews et al, 2013). Regarding sunlight, although direct exposure was not assessed in our study, patients were relatively short-stay inpatients at a primary care public hospital and we found no relationship between the duration of hospitalization and 25(OH)D levels, which again supports previous reports assessing the duration of hospitalization (Crews et al, 2013; Partti et al, 2012; Menkes et al, 2012), as well as direct sunlight exposure (Itzhaky et al, 2012). Similarly, in a previous study the variables of diet and exercise habits have also not been able to explain the differences between 25(OH)D levels in patients and control subjects (Berg et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding medication, in our patient sample we found no relationship between exposure to antipsychotic medication and 25(OH)D insufficiency, which is consistent with reports of patents with schizophrenia (Itzhaky et al, 2012), and of first-episode psychosis patients (Crews et al, 2013). Regarding sunlight, although direct exposure was not assessed in our study, patients were relatively short-stay inpatients at a primary care public hospital and we found no relationship between the duration of hospitalization and 25(OH)D levels, which again supports previous reports assessing the duration of hospitalization (Crews et al, 2013; Partti et al, 2012; Menkes et al, 2012), as well as direct sunlight exposure (Itzhaky et al, 2012). Similarly, in a previous study the variables of diet and exercise habits have also not been able to explain the differences between 25(OH)D levels in patients and control subjects (Berg et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…A number of small studies have also suggested that 25(OH)D deficits also extend into adulthood schizophrenia: Significantly lower circulating 25(OH)D levels have been reported in adult patients with chronic schizophrenia compared to other psychiatric patients (Humble et al, 2010; Menkes et al, 2012; Itzhaky et al, 2012) as well as healthy controls (Rey-Sánchez et al, 2009; Partti et al, 2010; Doknic et al, 2011; Itzhaky et al, 2012). The importance of 25(OH)D level maintenance in the adult population has also been highlighted by a large cohort study, from which it was reported that women with high dietary vitamin D consumption had a 37% lower risk of psychosis-like symptoms as compared to women with low consumption (Hedelin et al.…”
Section: Introductionmentioning
confidence: 99%
“…The difference, albeit with smaller magnitude, could be noticed for patients suffering from mental illnesses, too. Compared to our results, in some other societies there were much higher vitamin D serum levels and a lower prevalence of vitamin D deficiency in both in-and outpatients, including those with serious psychotic or depressive disorders (54)(55)(56). At present, the reasons for such differences are not completely understood but, at least in part, could be tied to the abovedescribed country's distinctions (20,21).…”
Section: Discussioncontrasting
confidence: 84%
“…Men typically develop schizophrenia about 5 years earlier than women 11 12. It has been shown that patients with psychiatric illness are much more likely to be vitD deficient than the general population; 13 14 patients with schizophrenia in particular are more likely to be deficient than individuals with other psychiatric disorders 10 15. Additionally, several well-established risk factors for the development of schizophrenia such as birth month, migration status and/or latitude of residency might all be related to vitD deficiency 16–18.…”
Section: Introductionmentioning
confidence: 99%